Investigation of the mechanisms of Angelica dahurica root extract-induced vasorelaxation in isolated rat aortic rings. Issue 1 (December 2015) - Lee, Kyungjin; Shin, Min; Ham, Inhye; Choi, Ho-Young
Abstract Background The root ofAngelica dahurica Bentham et Hooker (Umbelliferae) has been used as a traditional medicine for colds, headache, dizziness, toothache, supraorbital pain, nasal congestion, acne, ulcer, carbuncle, and rheumatism in China, Japan, and Korea. Interestingly, it has been used in the treatment of vascular diseases including hypertension. The aim of this study was to provide pharmacological evidence for the anti-hypertensive effect ofA. dahurica by investigating the mechanism underlying its vasorelaxant effect. Methods The vasorelaxant effects of a 70 % methanol extract of theA. dahurica root (ADE) on rat thoracic aorta and its underlying mechanisms were assessed. Isolated rat aortic rings were suspended in organ chambers containing 10 ml Krebs-Henseleit (K-H) solution and placed between 2 tungsten stirrups and connected to an isometric force transducer. Changes in tension were recorded via isometric transducers connected to a data acquisition system. Results ADE causes concentration-dependent relaxation in both endothelium-intact and endothelium-denuded aortic rings precontracted with phenylephrine (PE; 1 μM) or potassium (KCl; 60 mM) in K-H solution. And pre-treatment with ADE (1 mg/ml) inhibited calcium-induced vasocontraction of aortic rings induced by PE or KCl. However, ADE pre-treatment did not affect the contraction induced by PE or caffeine in Ca2+ -free K-H solution. Conclusions These results suggested that the ADE has vasorelaxant effect and the vasorelaxant activity is mediated by endothelium-independent pathway that includes the blockade of extracellular calcium influx through the receptor-operated Ca2+ channel and voltage-dependent calcium channel pathways.